Roles of intragenic and intergenic L1s in mouse and human. - Chumpol Ngamphiw; Sissades Tongsima; Apiwat Mutirangura (PLoS ONE, 2014)
Long INterspersed Element-1 (LINE-1 or L1) is a retrotransposable element that has shaped the evolution of mammalian genomes. There is increasing evidence that transcriptionally active L1 could have been co-opted through evolution to play various roles including X-inactivation, homologous recombination and gene regulation. Here, we compare putatively active L1 distributions in the mouse with human. L1 density is higher in the mouse except for the Y-chromosome. L1 density is the highest in X-chromosome, implying an X-inactivation role. L1 is more common outside genes (intergenic) except for the Y-chromosome in both species. The structure of mouse L1 is distinguished from human L1 by the presence of a 200 bp repeat in the 5' UTR of the former. We found that mouse intragenic L1 has significantly higher repeat copy numbers than intergenic L1, suggesting that this is important for control of L1 expression. Furthermore, a significant association between the presence of intragenic L1s and down-regulated genes in early embryogenesis was found in both species. In conclusion, the distribution of L1 in the mouse genome points to biological roles of L1 in mouse similar to human.